Cognitive predictors of incarcerated substance abusers' readiness to change - Bridget Robert. (2008)
The present study sought to determine the predictive validity of these specific cognitive factors – the substance abuser’s level of self-efficacy, his evaluation of the costs and benefits of continued substance use and the evaluation of his quality of life – on his readiness to change. Further, the study also aimed to shed light on how each of the predictor variables would differ in the continuum of an abuser’s readiness to change.